1992
DOI: 10.1007/bf00166700
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the position preference and nutritional state of individuals in schools of juvenile roach (Rutilus rutilus)

Abstract: Position preferences of well-fed and food-deprived juvenile roach were investigated in schools of 2 and 4 fish in the laboratory. Food-deprived fish appeared significantly more often in the front position than their well-fed conspecifics. For fish at the same hunger level, individuals at the front of the school had the highest feeding rate. These results represent the first evidence for a relationship between the nutritional state of individual fish and their positions in a school and suggest a functional adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 19 publications
8
125
1
Order By: Relevance
“…Previous work shows that the leading fishes of a school may be exposed to a higher predation risk (Bumann et al 1997) but will have first access to any resources encountered by the group (Krause et al 1992). Conversely, particularly in large schools in field conditions, fishes in the rear may experience reduced oxygenation due to oxygen consumption of the fishes ahead of them ( (2002) 1994).…”
Section: (B) School Dynamicsmentioning
confidence: 99%
“…Previous work shows that the leading fishes of a school may be exposed to a higher predation risk (Bumann et al 1997) but will have first access to any resources encountered by the group (Krause et al 1992). Conversely, particularly in large schools in field conditions, fishes in the rear may experience reduced oxygenation due to oxygen consumption of the fishes ahead of them ( (2002) 1994).…”
Section: (B) School Dynamicsmentioning
confidence: 99%
“…In addition to involving information uncertainty, most collective decisions, in practice, also involve conflicting 'preferences': that is, individual stakeholders in the decision often disagree as to what would constitute desirable decision outcomes in principle [27,28]. For example, in foraging decisions, males and females often prefer different types of forage [29,30]; hungry individuals often prefer different group activities and destinations from tired group members [24,27,[31][32][33]; and young or vulnerable animals often prefer safer areas than older, less vulnerable group members [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that hunger (condition) might play a role in position, with ®sh in poorer condition taking the lead, then dropping back to the shoal center when satiated. Such hunger-driven shoal structure has been demonstrated in shoaling herring (Robinson and Pitcher, 1989) and roach (Krause et al, 1992;Krause, 1993).…”
Section: Discussionmentioning
confidence: 98%